CCNA cloud CLDADM 210-455 - Jackson, Chris, 1973-; Safari eBooks ([Place of publication not identified] : Cisco Press, 2016)
"CCNA Cloud CLDADM 210-455 LiveLessons is a unique video product that provides a solid understanding of the key areas of knowledge required to pass the 210-455 Introducing Cisco Cloud Administration exam. This product walks the customer through each topic of the exam blueprint. Customers will gain knowledge of Cloud administration technologies, including Cloud fundamentals, Cloud technologies, Cloud administration and operations, Cloud monitoring and reporting, and Cloud troubleshooting. CCNA Cloud CLDADM 210-455 LiveLessons contains 5 modules with 16 independent video lessons, delivering more than 6 hours of instruction on this new Cisco exam. The videos contain detailed instructions for the exam, as well as live demos on Cisco and third-party Cloud solutions to both contextualize and explain concepts and products."--Resource description page.
Title from resource description page (viewed February 29, 2016).
Presenter, Chris Jackson.
Keywords: Computer networks -- Examinations -- Study guides; Electronic data processing personnel -- Certification; Electronic books